The Immediate Effects of Conventional Physical Therapy on the Knee Joint Load in Subjects with Moderate Knee Osteoarthritis; A Preliminary Single Blinded Randomized Control Trial - Leila Fattahi; Zahra Sadat Rezaeian (Shiraz University of Medical Sciences, 2015)
Background: Subjects with knee osteoarthritis typically have higher knee adduction moment. Current research efforts are mainly focused on therapeutic procedures that potentially may modify disease progression. This preliminary study was designed as a single blind (examiner) randomized control trial to investigate the impact of conventional physical therapy on pain, and knee joint load in subjects with moderate knee osteoarthritis. Methods: Twelve participants diagnosed with moderate knee OA were randomly assigned into control and intervention groups. Three-dimensional knee kinematic and kinetic data were recorded during the gait before and after 10 sessions of conventional physical therapy. In addition, pain intensity was evaluated by visual analog scale and pain subscale of KOOS questionnaire. The control group did not receive any intervention during the same period. Gait parameters were analyzed within and between groups using nonparametric tests. Results: There was a significant difference between groups in baseline KOOS-pain Score and ML knee force (P=0.048 and P=0.01). Immediately after ten sessions of physical therapy the initial (first) peak of knee adduction moment was significantly (P=0.03) lower than that of the control group while the first and second peak of knee AP velocity were significantly (P=0.02, P=0.01 respectively) higher. In the intervention group, the second peaks of vertical and anteroposterior (AP) knee forces were strongly correlated with the pretest KOOS-pain Score (r=0.99 and r=0.98, P<0.001). Therefore a multivariate general linear model was adopted with adjustment to baseline KOOS-pain. By this adjustment, 51% alleviation of VAS pain score and 81% decrement of first peak of knee adduction moment in comparison to control group was statistically significant (P=0.02, P=0.03 respectively). Conclusion: It seems that ten sessions of conventional physical therapy may modify knee joint load in subjects with moderate knee osteoarthritis. Further research is recommended.